THE FUNCTION OF IRONY AS A MEANS OF CREATING POLYSEMY AND MULTI-LAYERED TEXT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article deals with the role of irony as one of the most important literary devices that contribute to the creation of multilayered and multivalent text. Different functions of irony are analyzed: from comic to tragic, from hidden author's mockery to deep philosophical reflections. Special attention is paid to the specifics of Chekhov's irony, its manifestations in the relations between characters, in the author's position and in the symbolic system of the works. Examples from Anton Pavlovich Chekhov's works are given, demonstrating how irony helps to reveal hidden meanings, creating the effect of double reading of the text.